Nursing Care Systematization: Applicability to Primary Care (Acta Scientiarum. Health Sciences, 2020)
Nursing Care Systematization (NCS) is an organized and systematized process that concerns nursing professionals who provide quality assistance, being a mandatory tool in all health centers. Despite this factor, there is a visible resistance from nursing to the operationalization of a systematized care. Thus, the present study aims to analyze the applicability of nursing care systematization and the knowledge that primary care nurses have of this process. This is a descriptive, cross-sectional study with quanti-qualitative approach, conducted with nurses working in primary care teams from a regional health zone in the state of Paraná, Brazil. Out of the 44 participant nurses, only 20.5% claimed to take all steps in the nursing process during their care practice, and 43.2% do not know about the Resolution of the Federal Nursing Council that addresses NCS application. This low NCS applicability is worrisome, since it is related to the quality, resolution and security of care provision. The applicability of the systematization within the assessed teams is quite fragmented and small; besides, their NCS knowledge is insufficient considering that this is such a relevant tool to a nurse’s professional practice. It is possible to notice numerous fragilities and difficulties in the application of NCS to primary care, with highlight to time availability, overworked nurses, and need for training.